Simulated ΛCDM analogues of the thin plane of satellites around the Andromeda galaxy are not kinematically coherent structures - Buck, Tobias; Dutton, Aaron A.; Macciò, Andrea V. (Monthly notices of the Royal Astronomical Society, 2016)
Abstract. A large fraction of the dwarf satellites orbiting the Andromeda galaxy are surprisingly aligned in a thin, extended and apparently kinematically cohe